Assessment of symmetric dimethylarginine as a biomarker of renal function in hyperthyroid cats treated with radioiodine. (11th January 2019) - Buresova, Eva; Stock, Emmelie; Paepe, Dominique; Stammeleer, Lisa; Vandermeulen, Eva; Smets, Pascale; Duchateau, Luc; Lefebvre, Herve P.; Daminet, Sylvie
Abstract : Background: Measurement of serum creatinine (sCr) and urea nitrogen fail to detect decreased renal function in many hyperthyroid cats because of low muscle mass and glomerular hyperfiltration of affected cats. Serum symmetric dimethylarginine (sSDMA) is an earlier and more sensitive renal biomarker than sCr. Objective: Evaluate sSDMA as a biomarker of renal function in hyperthyroid cats before (T0) and 1 month after (T1) radioiodine ( 131 I) treatment. Animals: Forty‐seven client‐owned hyperthyroid nonazotemic cats were evaluated at T0 and T1. Methods: A prospective study in which sCr and sSDMA concentrations were determined in 47 hyperthyroid cats at T0 and at T1. Glomerular filtration rate (GFR) was estimated at T0 and T1 in 10 of these 47 cats using plasma exogenous creatinine clearance test. Results: Serum SDMA was elevated (>14 μg/dL) in 6 of 47 cats at T0 and normalized after treatment in 4 of those cats. All cats remained nonazotemic after treatment. In 10 cats in which GFR was measured, correlation between GFR and sSDMA was low and not significant (τb = −0.35, P = .17 at T0 and τb = −.22, P = .41 at T1), whereas correlation between GFR and sCr was moderate and significant (τb = −0.52, P < .05 at T0 and τb = −.53, P = <.05 at T1). Conclusions and Clinical Importance: Careful interpretation of mildly increased sSDMA with normal sCr in hyperthyroid cats is warranted as sSDMA values might normalize after resolution of hyperthyroidism in some cats. In this population of hyperthyroid cats, sSDMA was poorly correlated with GFR.